Inclusive education in Ghana: How prepared are the teachers? - Naami, Augustina; Mort, Kingsley Saa-Touh (Frontiers in Education, 2023)
We cannot overemphasize the importance of education in creating sustainable societies. Persons with disabilities continue to lag in education, which affects their employment and income and overall well-being. Education is necessary for persons with disabilities to break out of the cycle of poverty as recognized by both the United Nations Convention on the Rights of Persons with Disabilities and the Sustainable Development Goals. Ghana developed an inclusive education policy in 2015 with an overarching goal of fostering equitable access to education for all children. The critical question is what to teach. The B.Ed. Curriculum in 2018 was written to reform education and the school curriculum. But how prepared are student teachers at Colleges of Education in Ghana. Using the curriculum to promote inclusive education? In this paper, we use the social model of disability, anchored on the Sustainable Development Goals, to examine the preparedness of student teachers in meeting the needs of learners with diverse learning needs.